KONSEP MANAJEMEN PRODUKSI DAN DESAIN PEMASARAN PADA FILM FIKSI “CAKHRA KALA” - Robi’atul Yamania G; I Komang Arba Wirawan; Desak Putu Yogi Antari Tirta Yasa (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
The local film industry was on the brink of collapse in 2010 to 2011. The quality and theme of the film, which only pursued its sales without regard for the value it contained, is one of the reasons why Indonesia has lost interest in local films. Some observers note that the decline occurred as the saturated audience continues to be fed with the film formulaics. As a result, audiences' trust in the quality of Indonesian films was sparked. Furthermore, the perceived deficiencies from local films are the lack of managerial aspects of production regulated by the producer, as well as the resulting marketing plans. In this regard the writer formulates the problem that will be discussed in writing, which is the concept of production management and marketing design in the fictional film